ANALISIS PERBEDAAN KINERJA KEUANGAN BANK UMUM KONVENSIONAL DAN BANK UMUM SYARIAH DI INDONESIA TAHUN 2016-2021 (STUDI KASUS BANK BRI KONVENSIONAL DAN BANK BRI SYARIAH): ANALISIS PERBEDAAN KINERJA KEUANGAN BANK UMUM KONVENSIONAL DAN BANK UMUM SYARIAH DI INDONESIA TAHUN 2016-2021 (STUDI KASUS BANK BRI KONVENSIONAL DAN BANK BRI SYARIAH) - Safitri, Vita Aprilia; Indaryani, Mamik; Sunarno (Journal of Principles Management and Business, 2023)
This research aims to analyze the differences in the financial performance of conventional commercial banks and sharia commercial banks in Indonesia in 2016-2021 using financial ratios. The financial ratios used in this research are CAR, NPL, BOPO, LDR, ROA and ROE. The type of research used in this research is quantitative research. The data source used in this study is documentation by collecting scientific journals and previous research. The data used in this research is financial report data from conventional commercial banks and sharia commercial banks from 2016 to 2021 obtained from the official website of the bank concerned. The sampling method in this research is purposive sampling, based on the conditions that must be met, the sample obtained in this research is Bank BRI Conventional and Bank BRI Syariah. The data analysis technique used in this research is the t test for the difference between two means. The results of the analysis show that there are differences between the financial performance of Bank BRI Conventional and Bank BRI Syariah. Based on the analysis of differences in financial performance carried out, the results showed that the CAR, NPL and BOPO financial ratios of Conventional BRI Bank were smaller than BRI Syariah Bank, while the LDR, ROA and ROE financial ratios of Conventional BRI Bank were greater than BRI Syariah Bank.